Pengaruh Punishment dan Reward terhadap Motivasi Kerja Serta Dampaknya terhadap Kinerja Karyawan pada PT. Bank Pembangunan Daerah Jambi Kantor Cabang Utama - Alfijr Ashraf; Arna Suryani; Sudirman Sudirman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine the state or description of Punishment, Reward, motivation and employee performance as well as to determine and analyze the influence of Punishment and Reward through motivation on employee performance at PT. Bank Pembangunan Daerah Jambi Main Branch Office. This type of research uses descriptive verification research. This study uses the PLS analysis method. The results of this study reveal that Punishment has a positive and significant effect on motivation at PT. Bank Pembangunan Daerah Jambi Main Branch Office. In addition, Reward also has a positive and significant effect on motivation. Punishment also has a positive and significant effect on employee performance, However, Reward does not have a significant effect on employee performance, which indicates that increasing Reward has not had a significant direct impact on improving employee performance. Furthermore, motivation has a positive and significant effect on employee performance. In addition to its direct effect, Punishment also has a positive and significant effect on employee performance through motivation, which means that increasing Punishment can increase work motivation and ultimately have an impact on improving employee performance. Likewise, Reward has a positive and significant effect on employee performance through motivation, which indicates that better Rewards can increase employee motivation so that it has an impact on improving employee performance at PT. Bank Pembangunan Daerah Jambi Main Branch Office..